Winter Soil Warming Exacerbates the Impacts of Spring Low Temperature Stress on Wheat. (24th May 2016) - Li, X.; Jiang, D.; Liu, F.
Abstract: The increase in global mean air temperature is likely to affect the soil temperatures in agricultural areas. This study aims to study the effects of winter soil warming on the responses of wheat to low temperature stress in spring. Wheat plants were grown under either normal or increased soil temperature by 2.5 °C for 82 days in winter. The physiological and yield responses of the plants to a 2‐day low temperature stress (4/2 °C in the day/night) at jointing stage were investigated. After exposing to low spring temperature, the plants that had experienced winter soil warming showed lower leaf and root water potential, lower oxygen scavenging capacity and poor photosynthetic performance as compared with the plants grown under normal soil temperature during winter. WL plants had significantly lower sugar content in shoot than the CL plants, which might have contributed to their higher susceptibility to low temperature. In addition, winter soil warming exacerbated the negative effects of low spring temperature on grain yield.